Vegetal polymer in repair of defects of the orbital floor: an experimental study in rabbits - Schellini, Silvana Artioli [UNESP]; Nunes, Elifas L. [UNESP]; Pellizzon, Claudia Helena [UNESP]; Hirai, Flavio E.; Schellini, Ricardo C. [UNESP]; Padovani, Carlos Roberto [UNESP] (Wiley-Blackwell, 2012)
Background: An experimental study was done to assess the ability of the vegetal polymer miniplates and screws to repair defects of the orbital floor.Methods: An artificial standard-sized defect was created in the bony floor of right orbit of 45 albino rabbits. The animals were divided into three experimental groups: control group (G1) involving animals with orbital floor defect and no treatment; titanium group (G2) containing animals with orbital floor defect repaired by titanium miniplates and screws; vegetal polymer group (G3) composed of animals with similar orbital floor defects repaired by vegetal polymer miniplates and screws. Throughout the course of the experiment, the animals were clinically evaluated. At 15, 30 and 60 days after surgery, the animals were killed. They were X-rayed immediately after the floor defect and at the moment of sacrifice. Histological and morphometric evaluation of inflammatory reaction and bone healing was done. Data were statistically evaluated.Results: No implants were extruded. Bone consolidation was similar in G2 and G3 and better than in G1 group animals. Inflammatory reaction was most pronounced in animals of G3 15 days after surgery, and it subsided over time.Conclusion: Vegetal polymer miniplates and screws induces small inflammatory reaction and had the ability to stimulate bone growth with good integration in the orbital floor defect allowing to consider the vegetal polymer adequate option to treat orbital floor defects. Future studies involving long-term follow-up and biomechanical tests to evaluate material resistance to traction are needed.
Keywords: histologic study; orbital fracture; radiologic study; titanium; vegetal polymer